Pembatasan Sosial Berskala Besar (PSBB) Dan Pidana Denda Dalam Rangka Pencegahan dan Pemberantasan Pandemi Coronavirus Disease (Covid)-19 - Kartono, Kartono (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe trend of the spread of Coronavirus (Covid)-19 which continues to soar has an impact on society for health, peace and safety of the soul.Â Public awareness and compliance with laws and regulations and the government's call for a Large-Scale Social Restrictions (PSBB) policy are important not to be violated or ignored.Â The application of criminal sanctions for fines is an alternative sanction in law enforcement so that people are deterred, educated and as a means of government social control. The research method is normative juridical supported by empirical research using secondary data in the form of books, legislation and the internet. Type of qualitative research. The results of the study concluded that the government must be firm in applying criminal sanctions and criminal fines as an alternative to making people deterrent, educated and as a means of social controlÂ Keywords: PSBB, Criminal Fines, Prevention.